Accuracy of premium calculation models for CAT bonds: An empirical analysis - Marcello Galeotti; Marc Gürtler; Christine Winkelvos (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2009)
CAT bonds are of significant importance in the field of alternative risk transfer. Since the market of CAT bonds is not complete, the application of an appropriate pricing model is of high relevance. We apply different premium calculation models in order to compare them with regard to their predictive power. Without taking the financial crisis into account, a version of the Wang transformation model and the linear model are the most accurate ones. In contrast, under consideration of the financial crisis, all analyzed models are approximately equivalent. Furthermore, we find that CAT bond specific information does not improve out-of-sample results.
Keywords: G13; G22; 330; CAT Bonds; Alternative Risk Transfer; Premium Calculation Models; Empirical Analysis